Management Strategies for Restless Legs Syndrome/Willis-Ekbom Disease During Pregnancy - Garbazza, Corrado; Manconi, Mauro (Sleep medicine clinics, 2018)
Restless legs syndrome/Willis-Ekbom disease is a common disorder during pregnancy that may significantly impact on the health of affected women, leading to negative consequences in the short and long term. An accurate diagnosis helps to recognize the syndrome and choose the optimal therapeutic strategy, based on the characteristics and needs of the patient. This article summarizes the main treatment options recommended by the consensus clinical guidelines of the International Restless Legs Syndrome Study Group and provides a short guide to the management of restless leg syndrome during pregnancy in clinical practice.